On the role of flexibility in linker-mediated DNA hydrogels. Issue 4 (19th December 2019) - Stoev, Iliya D.; Cao, Tianyang; Caciagli, Alessio; Yu, Jiaming; Ness, Christopher; Liu, Ren; Ghosh, Rini; O'Neill, Thomas; Liu, Dongsheng; Eiser, Erika
Abstract : DNA nanostars with sticky, single-stranded DNA overhangs, are known to form thermally reversible, viscoelastic networks. Here we show that introducing the right flexibility will rather lead to a cluster phase with a much reduced viscosity then an elastic hydrogel. Abstract : Three-dimensional DNA networks, composed of tri- or higher valent nanostars with sticky, single-stranded DNA overhangs, have been previously studied in the context of designing thermally responsive, viscoelastic hydrogels. In this work, we use linker-mediated gels, where the sticky ends of two trivalent nanostars are connected through the complementary sticky ends of a linear DNA duplex. We can design this connection to be either rigid or flexible by introducing flexible, non-binding bases. The additional flexibility provided by these non-binding bases influences the effective elasticity of the percolating gel formed at low temperatures. Here we show that by choosing the right length of the linear duplex and non-binding flexible joints, we obtain a completely different phase behaviour to that observed for rigid linkers. In particular, we use dynamic light scattering as a microrheological tool to monitor the self-assembly of DNA nanostars with linear linkers as a function of temperature. While we observe classical gelation when using rigid linkers, the presence of flexible joints leads to a cluster fluid with a much-reduced viscosity. Using both the oxDNA model and a coarse-grained simulation to investigate the nanostar-linker topology, we hypothesise on the possible structure formed by the DNA clusters. Moreover, we present a systematic study of the strong viscosity increase of aqueous solutions in the presence of these DNA building blocks.